1998
DOI: 10.1074/jbc.273.12.7072
|View full text |Cite
|
Sign up to set email alerts
|

Activation of STAT3 by the c-Fes Protein-tyrosine Kinase

Abstract: STATs (signal transducers and activators of transcription) are a class of transcription factors with SH2 domains that are activated in response to tyrosine phosphorylation. STATs are often activated by members of the JAK family of protein-tyrosine kinases in response to cytokine stimulation. The activation mechanism involves SH2-dependent recruitment of the STATs to tyrosine-phosphorylated cytokine receptors. The STATs are then phosphorylated by receptor-associated JAKs, which induces dimerization via reciproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 33 publications
(37 reference statements)
4
56
0
Order By: Relevance
“…The most prominent example is v-Src that induces a constitutive activation of STAT3 in the absence of cytokine stimulations (Yu et al, 1995;Cao et al, 1996). PTK other than Src, such as Lck and v-Fps/Fes activate STAT3 and STAT5 in T cells and fibroblasts, respectively (Cirri et al, 1997;Nelson et al, 1998;Lund et al, 1999). In the mouse T-cell lymphoma cell line LYSTRA that overexpresses Lck, both DNA binding activities and tyrosine phosphorylation of STAT3 and STAT5, but not STAT1, are enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent example is v-Src that induces a constitutive activation of STAT3 in the absence of cytokine stimulations (Yu et al, 1995;Cao et al, 1996). PTK other than Src, such as Lck and v-Fps/Fes activate STAT3 and STAT5 in T cells and fibroblasts, respectively (Cirri et al, 1997;Nelson et al, 1998;Lund et al, 1999). In the mouse T-cell lymphoma cell line LYSTRA that overexpresses Lck, both DNA binding activities and tyrosine phosphorylation of STAT3 and STAT5, but not STAT1, are enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Several other kinases have been implicated in the phosphorylation of STAT3, including members of the Src family (hck, src), Erb2, anaplastic lymphoma kinase, protein kinase C-␊, c-fes, and epidermal growth factor receptor (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Whether any of these kinases are active in MM cells, and which of these kinases is activated by IL-6, is not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…Fes expression is su cient to induce di erentiation of K-562 myeloid leukemia cells (Cheng et al, 1999;Yu et al, 1989) and may be required for di erentiation and survival signaling in other myeloid cell lines (Manfredini et al, 1993(Manfredini et al, , 1997. We have observed that Fes strongly induces Stat3 activation following co-expression of the proteins in either 293T cells or using a baculovirus/Sf-9 cell system (Nelson et al, 1998). In addition, expression of constitutively active mutants of Fes is su cient to induce survival and di erentiation responses in the GM-CSF-dependent cell line, TF-1 (Cheng H and Smithgall TE, unpublished data).…”
Section: Stat Activation By Src Kinases In Myeloid Cell Survivalmentioning
confidence: 99%